Neutral point potential balance algorithm for three-level NPC inverter based on SHEPWM - Zhang, Xiao-hua; Yue, Wen-kai (Electronics letters, 2017)
In order to obtain the capability of neutral point potential balancing with low switching frequency, a novel balance control algorithm for neutral-point-clamped (NPC) three-level inverter based on Selective harmonic elimination pulse-width modulation (SHEPWM) are proposed. On the basis of the switch sequences and voltage vector action angle corresponding to the three-phase SHEPWM waveform at different modulation index, the three kinds of redundant vector adjustment schemes are designed. Then, load current and neutral point potential feedback to the controller, and the three-phase pulse-width modulation signal adjusted directly by the hysteresis controller to realise neutral point potential balance. Experimental results show that different redundant vector adjustment schemes have different neutral point potential balancing speed and average switching frequency, but do not affect the harmonic elimination ability of the line voltage.